2019
DOI: 10.1111/medu.13934
|View full text |Cite
|
Sign up to set email alerts
|

Emotional challenges of medical students generate feelings of uncertainty

Abstract: Objectives Health care students face many situations during their education that might be emotionally challenging. Students are confronted with illness, suffering, death, patient treatment dilemmas, and witnessing unprofessional behaviour on the part of health care professionals. Few studies have focused on what these experiences lead to in relation to the process of becoming a professional. The purpose of the study was to explore medical students’ main concerns relating to emotionally challenging situations d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 49 publications
(79 reference statements)
2
45
0
1
Order By: Relevance
“…The need to adapt to new environments is one of the challenging elements of medical students' educational journey. (7,19) The relative lack of tolerance for uncertainty and ambiguity has been found to be an important predictor of psychological distress among medical students. (20) Our study showed that approximately 45% of surveyed students had higher stress levels than usual during the pandemic ( Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…The need to adapt to new environments is one of the challenging elements of medical students' educational journey. (7,19) The relative lack of tolerance for uncertainty and ambiguity has been found to be an important predictor of psychological distress among medical students. (20) Our study showed that approximately 45% of surveyed students had higher stress levels than usual during the pandemic ( Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…The need to adapt to new environments is one of the challenging elements of medical students' educational journey. (7,21) The relative lack of tolerance for uncertainty and ambiguity has been found to be an important predictor of psychological distress among medical students. (22) Our study showed that approximately 45% of surveyed students had higher stress levels than usual during the pandemic ( Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Students in medical school face challenges such as the huge amount of information they need to learn and emotionally challenging situations they are confronted with such as illness, suffering, and patient treatment dilemmas, which cause them feelings of uncertainty about possessing insufficient knowledge and skills [1].…”
Section: Introductionmentioning
confidence: 99%